Impact of the use of immunoglobulin palivizumab in the State of São Paulo: a cohort study - Ivana Regina Gonçalves; Marli Teresinha Cassamassimo Duarte; Helio Rubens de Carvalho Nunes; Rubia de Aguiar Alencar; Cristina Maria Garcia de Lima Parada (Universidade de São Paulo, 2017)
ABSTRACT Introduction: the use of palivizumab as prophylaxis of the respiratory syncytial virus is not a consensus. In Brazil, it is a public health program, but other countries do not consider it cost-effective. Objective: to identify the rate of hospitalization in Intensive Care Unit for respiratory illness or symptoms among children who received the immunoglobulin palivizumab, the proportion of children who failed to take any of the recommended doses and the impact of that failure on hospitalization. Method: cohort study conducted with 693 children enrolled in the palivizumab program in 2014 (85.1% of the population), with monthly assessment from April to September through a telephone call to the mothers or caregiver. The probability of hospitalization in the Intensive Care Unit related to failure in taking the palivizumab, was analyzed through multiple logistic regression, with p<0,05. Results: the hospitalization rate was 18.2%; 2.3% of the children did not receive all the recommended immunoglobulin doses; the probability of hospitalization for respiratory illness or symptoms increased by an average of 29% at each missed dose (p=0.007; OR=1.29, CI=1.07-1.56). Conclusion: the increase in the chance of hospitalization related to missed immunoglobulin doses indicates the need to implement health education actions and active search for absent children by the health services.